2011
DOI: 10.1093/ecam/nep130
|View full text |Cite
|
Sign up to set email alerts
|

Iyengar Yoga versus Enhanced Usual Care on Blood Pressure in Patients with Prehypertension to Stage I Hypertension: a Randomized Controlled Trial

Abstract: The prevalence of prehypertension and Stage 1 hypertension continues to increase despite being amenable to non-pharmacologic interventions. Iyengar yoga (IY) has been purported to reduce blood pressure (BP) though evidence from randomized trials is lacking. We conducted a randomized controlled trial to assess the effects of 12 weeks of IY versus enhanced usual care (EUC) (based on individual dietary adjustment) on 24-h ambulatory BP in yoga-naïve adults with untreated prehypertension or Stage 1 hypertension. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 25 publications
4
78
0
4
Order By: Relevance
“…Two small randomized studies of hatha yoga-type practices evaluated BP as an outcome since 2007. 60,61 A third small trial assessed the impact of a variation of pranayama on a background of hatha yoga practice. In a randomized, controlled clinical trial, yoga-naïve adults with stage I hypertension were randomized to 12 weeks of Iyengar yoga or control arms (enhanced usual care emphasizing diet).…”
Section: Recent Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two small randomized studies of hatha yoga-type practices evaluated BP as an outcome since 2007. 60,61 A third small trial assessed the impact of a variation of pranayama on a background of hatha yoga practice. In a randomized, controlled clinical trial, yoga-naïve adults with stage I hypertension were randomized to 12 weeks of Iyengar yoga or control arms (enhanced usual care emphasizing diet).…”
Section: Recent Trialsmentioning
confidence: 99%
“…In a randomized, controlled clinical trial, yoga-naïve adults with stage I hypertension were randomized to 12 weeks of Iyengar yoga or control arms (enhanced usual care emphasizing diet). 60 In total, 26 and 31 individuals in the yoga and control arms, respectively, completed the study. In the control group, 24-hour systolic, diastolic, and mean arterial pressure BPs decreased significantly by 5, 3, and 3 mm Hg, respectively, from baseline to 6 weeks (P<0.05 versus baseline) and 4, 2, and 2 mm Hg at 12 weeks (P=NS versus baseline).…”
Section: Recent Trialsmentioning
confidence: 99%
“…4,18 Similarly, regular practice of Yoga with use of low-fat vegetarian diet resulted in retardation of progression and even regression of coronary obstructions as compared to usual care control group in angiographic ally detected coronary artery disease. 7,18,24 Small clinical trials have shown benefits of yoga in patients with diabetes, 3,10 and a systematic review found that yoga improved metabolic risk factors. 9 Integrated yoga program has been shown to be helpful in reducing both post-chemotherapy nausea and anticipatory nausea and vomiting.…”
Section: Yoga In Diseasementioning
confidence: 99%
“…O ioga é uma forma de atividade física que consiste na prática de várias técnicas incluindo posturas (asanas), técnicas respiratórias (pranayamas) e meditação (COHEN et al, 2011). De forma complementar, Miles et al (2013) afirmam que o ioga é qualitativamente diferente de qualquer outro modo de atividade física que consiste em uma combinação única de contrações musculares isométricas, alongamentos musculares, técnicas de relaxamento e exercícios respiratórios.…”
Section: Introductionunclassified